METHODOLOGICAL AND APPLIED PROVISIONS OF ECONOMIC MOBILITY AS CONDITIONS FOR ENSURING THE ECONOMIC SECURITY OF ENTERPRISES IN CRISIS CONDITIONS - VASYLTSIV, Taras; VYHOVSKY, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study revealed the relevance of the problem of ensuring economic mobility and economic security of domestic enterprises. The purpose of the study is to substantiate the theoretical and applied principles of managing economic mobility in the system of ensuring the economic security of enterprises in a complex socio-economic environment. It is emphasized that modern processes of globalization, scientific and technical progress, spread of information technologies create favorable conditions for the mobility of resources. It was established that one of the most relevant modern research concepts is the economic mobility of enterprises, with a special emphasis on ensuring the economic security of economic entities. It was concluded that the economic mobility of the enterprise is its ability to respond and adapt to new challenges of a changing environment with decision-making regarding changes in specialization, geography and forms of activity. The main types of economic mobility are defined, which reflect changes as a consequent reaction and adaptation of the enterprise to the challenges of a changing environment. A typical scheme of economic mobility of an enterprise as a cause-and-effect process has been developed. The main types and forms of economic mobility of enterprises, which are relevant to research in modern crisis conditions, are considered. The directions and objects of diversification of the company's activity have been determined. Methods of corporate migration and relocation of enterprises are indicated, their specifics, advantages and opportunities are outlined. It was concluded that the economic mobility of the enterprise depends on many factors of the external changing environment, but primarily on its own characteristics. Among them is the size that determines the resource possibilities of specialization, geography and forms of activity. Since the basis of economic development is small and medium-sized enterprises, it is necessary to separately investigate the features of economic mobility and the tools for its strengthening in this business category. Small and medium-sized enterprises are more vulnerable to crises. Therefore, increasing their mobility will allow mitigating the crisis reactions of the economy and society.
Keywords: economic mobility; economy and enterprise management; economic security; risks and threats; crisis conditions